Characterization and virulence of yeasts associated with neonatal thrush - Eman G. A. M. El-Dawy; Abeer Baddar; Youssuf A. Gherbawy; Asmaa S. Yassein (BMC Microbiology)
Abstract Background Species of Candida are the main cause of aggressive fungal infections in preterm newborns. These infections are linked to significant illness and death. Neonatal thrush is diagnosed by observing white patches on the surfaces of the mucosa of the mouth. Yeast is often associated with it. This study aimed to apply different techniques to characterize the yeasts associated with neonatal mouth thrush. Laboratory-based yeast species identification techniques (morphological and molecular) have been employed. Virulence genes were tested to compare experimental virulence assays and the presence of studied genes. Results Our results indicated that forty-one isolates out of 79 were identified as C. albicans and confirmed by using (CALB1-CALB2) specific primers. C. dubliniensis, C. glabrata (Nakaseomyces glabratus), C. guilliermondii (Meyerozyma guilliermondii), C. krusei (Pichia kudriavzevii), C. lusitaniae (Clavispora lusitaniae), C. parapsilosis, C. tropicalis, C. kefyr (Kluyveromyces marxianus), and Trichosporon asahii were also verified by applying (CandF - CandR) primer and Internal transcribed spacer (ITS) sequencing. Thirty-six isolates were active producers of the three tested enzymes: hemolysin, phospholipase, and proteinase. Fifty-five isolates secreted hemolysin, and sixty-four isolates were positive for the presence of the phospholipase B1 (PLB1) gene. The secreted aspartyl protease 1 (SAP1) gene was detected in thirty-three isolates, from which thirty-two isolates secreted the proteinase enzyme. Conclusion Different techniques were required to diagnose the Candida species and other yeasts associated with neonatal thrush. C. albicans was the dominant species. The identification of two species of C. albicans and C. dubliniensis by specific primer (CALB1-CALB2), general primer (CandF - CandR), and sequencing techniques was applied in this study.